The Futures are Unwritten- Vol. 1- THE MAG- Vol. 2- The Guide : 56th International Art Exhibition- La Biennale di Venezia 2015 (Venice; Marsilio Editori, 2015)
The BAG, Biennale Arte Guide. The MAG.
English
Keywords: Biennial Guidebook; N4390-5098 Visual Arts- Exhibitions; Italy